Plutarch in the religious and philosophical discourse of late antiquity - Roig Lanzillotta, Lautaro; Munoz Gallarte, Israel; Plutarchus 45-120 (Studies in Platonism, Neoplatonism, and the Platonic tradition, 2012)
Introduction: Plutarch at the crossroads of religion and philosophy / Lautaro Roig Lanzillotta -- Plutarch and philosophy -- Plutarch on the sleeping soul and the waking intellect and Aristotle's double entelechy concept / Abraham P. Bos -- The doctrine of the passions: Plutarch, Posidonius and Galen / Francesco Becchi -- The adventitious motion of the soul (Plut., Stoic. repugn. 23, 1045b-f) and the controversy between Aristo of Chios and the middle academy / Raul Caballero -- Plutarch and "pagan monotheism" / Frederick Brenk -- Socrates and Alcibiades: a notorious skandalon in the later Platonist tradition / Geert Roskam -- Salt in the holy water : Plutarch's Quaestiones naturales in Michael Psellus' De omnifaria doctrina / Michiel Meeusen -- Plutarch and religion -- Iacchus in Plutarch / Ana Isabel Jimenez San Cristobal -- Plutarch's idea of god in the religious and philosophical context of late antiquity / Lautaro Roig Lanzillotta -- Plutarch as Apollo's priest at Delphi / Angelo Casanova -- Plutarch's attitude towards astral biology / Aurelio Perez Jimenez -- "Cicalata sul fascino volgarmente detto jettatura": Plutarch, Quaestio convivalis 5.7 / Paola Volpe Cacciatore -- The Eleusinian mysteries and political timing in the life of Alcibiades / Delfim F. Leao -- Mysteriodes theologia: Plutarch's Fr. 157 Sandbach between cultual traditions and philosophical models / Rosario Scannapieco -- A non-fideistic interpretation of 'pistis' in Plutarch's writings: the harmony between 'pistis' and knowledge / George van Kooten -- The colors of the souls / Israel Munoz Gallarte